Witness Literature in Byzantium - Goldwyn, Adam J. author. aut Link
XVI, 299 p. 1 illus.
Keywords: “By turns reflexive and daring, Goldwyn's book is riskful thinking at its best. For medievalists, it opens up new possibilities for reading and teaching the works that matter to us most -- those that somehow place us face-to-face with human Others and leave us feeling more than we can express. In Goldwyn's book, the face of the human Other presents itself, even if only briefly and in a moment of mortal danger.” — Vincent Barletta, Stanford University, USA “Innovative, illuminating and daring. This theoretically sophisticated book revolutionizes the study of Byzantine literature and enriches our understanding of angst, anxiety and trauma in the middle ages. This book provides an insightful discussion of captivity in the Byzantine era and a new interdisciplinary, trans-historical understanding of narratives which will captivate scholars for years to come.” —Elena N. Boeck, DePaul University, USA.